PERAN DAN METODE PENDAMPINGAN REMAJA KATOLIK DI PAROKI SANTA MARIA JOMBANG - Dato, Sopiana; Ardijanto, Don Bosco Karnan (CREDENDUM: Jurnal Pendidikan Agama, 2019)
This research aims to explore the roles and mentoring methods of Catholic adolescent facilitators in the Santa Maria Jombang Parish. Utilizing a qualitative methodology, the study involved purposive sampling to select informants, comprising both facilitators and adolescents. Data collection was conducted through voice call interviews. The findings reveal four key conclusions: first, the facilitators are recognized as adults who play a vital role in nurturing and accompanying Catholic adolescents, embodying their vocation and mission; second, a variety of mentoring methods are employed by the facilitators; third, adolescents perceive that their facilitators align with their expectations due to their personalities and spirituality; and fourth, there are specific mentoring methods that adolescents prefer or dislike. This study highlights the importance of effective mentorship in the spiritual development of Catholic youth.